Cell necrosis–independent sustained mitochondrial and nuclear DNA release following trauma surgery. Issue 2 (February 2015) - McIlroy, Daniel J.; Bigland, Mark; White, Amanda E.; Hardy, Benjamin M.; Lott, Natalie; Smith, Doug W.; Balogh, Zsolt J.
Abstract : BACKGROUND: Mitochondrial DNA (mtDNA), a potent proinflammatory damage-associated molecular pattern, is released in large titers following trauma. The effect of trauma surgery on mtDNA concentration is unknown. We hypothesized that mtDNA and nuclear DNA (nDNA) levels would increase proportionately with the magnitude of surgery and both would then decrease rapidly. METHODS: In this prospective pilot, plasma was sampled from 35 trauma patients requiring orthopedic surgical intervention at six perioperative time points. Healthy control subjects (n = 20) were sampled. DNA was extracted, and the mtDNA and nDNA were assessed using quantitative polymerase chain reaction. Markers of cell necrosis were also assayed (creatine kinase, lactate dehydrogenase, and aspartate aminotransferase). RESULTS: The free plasma mtDNA and nDNA levels (ng/mL) were increased in trauma patients compared with healthy controls at all time points (mtDNA: preoperative period, 108 [46–284]; postoperative period, 96 [29–200]; 7 hours postoperatively, 88 [43–178]; 24 hours, 79 [36–172]; 3 days, 136 [65–263]; 5 days, 166 [101–434] [healthy controls, 11 (5–19)]) (nDNA: preoperative period, 52 [25–130]; postoperative period, 100 [35–208]; 7 hours postoperatively, 75 [36–139]; 24 hours postoperatively, 85 [47–133]; 3 days, 79 [48–117]; 5 days, 99 [41–154] [healthy controls, 29 (16–54)]). Elevated DNA levels did not correlate with markers of cellular necrosis. mtDNA was significantly elevated compared with nDNA at preoperative period ( p = 0.003), 3 days ( p = 0.003), and 5 days ( p = 0.0014). Preoperative mtDNA levels were greater with shorter time from injury to surgery ( p = 0.0085). Postoperative mtDNA level negatively correlated with intraoperative crystalloid infusion ( p = 0.0017). Major pelvic surgery (vs. minor) was associated with greater mtDNA release 5 days postoperatively ( p < 0.05). CONCLUSION: This pilot of heterogeneous orthopedic trauma patients showed that the release of mtDNA and nDNA is sustained for 5 days following orthopedic trauma surgery. Postoperative, circulating DNA is not associated with markers of tissue necrosis but is associated with surgical invasiveness and is inversely related to intraoperative fluid administration. Sustained elevation of mtDNA levels could be of inflammatory origin and may contribute to postinjury dysfunctional inflammation. LEVEL OF EVIDENCE: Prospective study, level III. Abstract : Supplemental digital content is available in the text.